de Verdal et al. Optimization of multi-generation multi-location genomic prediction models for recurrent genomic selection in an upland rice population - Verdal, Hugues de; Baertschi, Cédric; Frouin, Julien; Quintero Valencia, Constanza Maria; Ospina Rey, Yolima; Álvarez Vargas, Maria Fernanda; Cao, Tuong-Vi Cao; Bartholomé, Jérôme; Grenier, Cécile (2023)
These data correspond to the phenotypic and genomic datafiles used for the paper entitled "Optimization of multi-generation multi-location genomic prediction models for recurrent genomic selection in an upland rice population"